Long-Term Investigation of a Borehole Heat Exchanger (BHE) Array with the Influence of Same Inlet Temperature (SIT) and Same Heat Load (SHL) Boundaries - Yuping Zhang; Xiao Yang; Jun Liu; Boyang Liu; Fujiao Tang; Hossein Nowamooz (Advances in Civil Engineering)
Borehole heat exchanger (BHE) array is a key element in the ground source heat pump system (GSHPS). The BHE array is traditionally simplified by assuming the same heat exchange rate for each BHE, which normally is not correspondent to the real applications. In this investigation, a TRT was firstly conducted for a site located in Shanxi Province (China) to get the local ground thermal properties. A numerical simulation framework was next verified by the TRT results. Subsequently, the ground thermal properties obtained by the TRT were used in the numerical simulation model to investigate the influence of two operation strategies on the ground temperature development of the surrounding soil and the BHE performance. The results showed that both ground temperature and BHE array performance decreased during the 8-year operation period of the BHE array in the heating mode. The ground temperature around the center BHE was lower in the same heat load (SHL) scenario (same heat load for the BHEs in the array) than in the same inlet temperature (SIT) scenario (same carrying fluid inlet temperature for the BHEs in the array), and this difference can be 2 °C in the 7th year. The annual average outlet temperature in the SHL scenario was also lower than that in the SIT scenario, especially in the long term. The investigation shows that SIT working strategy superiors the SHL strategy, providing a reference for the upcoming investigation on the design aspect of the GSHPS.